Substance P, vasoactive intestinal peptide and nerve growth factor involvement in the pathogenesis of few dermatoses - Teresiak, Ewa (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
Neuropeptides act as neuromodulators, neurotransmitters, neurotrophins and neurohormons and are involved in the transmission of signals between nerve cells and immune cells. They are produced mostly in afferent, unmyelinated C fibres or myelinated A delta fibres, in response to nociceptive stimulation as well as in fibres of autonomic nervous system. The role of neuropeptides in pathogenesis of neurogenic skin inflammation is not completely understood. In spite of some controversies, most of authors agree that neuropeptides play an important role in development and supporting neurogenic inflammation within the skin in the course of such chronic skin diseases as atopic dermatitis, psoriasis or eczema. SP and VIP involvement in the pathogenesis of atopic dermatitis results from their increased concentration in plasma or serum, increased number of SP and VIP – positive nerve fibres in lesional skin, promotion of differentiation of T cells towards Th2 or Th1 characteristics, as well as influence on proinflammatory cytokine profile production. SP and VIP involvement in the pathogenesis of psoriasis and eczema results from increased SP or VIP skin innervation. An increased proliferation of keratinocytes caused by these neuropeptides has been observed in psoriasis as well as an increase in proinflammatory cytokine production. An increased number, activation and proliferation of lymphocytes Th2 releasing NGF, suggest an important role of NGF in the pathogenesis of atopic dermatitis. Epidermal thickness correlates with the intensity of NGF expression both in psoriasis and atopic dermatitis. NGF levels are increased in psoriatic as compared to nonlesional and normal skin and psoriatic keratinocytes express higher amounts of NGF than normal keratinocytes. An increased expression of NGF receptors and hyperthrophy of nerve fibres in psoriatic lesions has also been observed.